Substituted Phthalic Anhydrides from Biobased Furanics: A New Approach to Renewable Aromatics - Thiyagarajan, Shanmugam; Genuino, Homer C.; Śliwa, Michał; van der Waal, Jan C.; de Jong, Ed; van Haveren, Jacco; Weckhuysen, Bert M.; Bruijnincx, Pieter C. A.; van Es, Daan S. (ChemSusChem, 2015)
A novel route for the production of renewable aromatic chemicals, particularly substituted phthalic acid anhydrides, is presented. The classical two‐step approach to furanics‐derived aromatics via Diels–Alder (DA) aromatization has been modified into a three‐step procedure to address the general issue of the reversible nature of the intermediate DA addition step. The new sequence involves DA addition, followed by a mild hydrogenation step to obtain a stable oxanorbornane intermediate in high yield and purity. Subsequent one‐pot, liquid‐phase dehydration and dehydrogenation of the hydrogenated adduct using a physical mixture of acidic zeolites or resins in combination with metal on a carbon support then allows aromatization with yields as high as 84 % of total aromatics under relatively mild conditions. The mechanism of the final aromatization reaction step unexpectedly involves a lactone as primary intermediate. Er zit een Aldertje onder het gras: The classical two‐step approach to furanics‐derived aromatics, via Diels–Alder (DA) aromatization, is modified into a three‐step procedure to avoid retro‐DA reactions. The new sequence involves a mild hydrogenation step to obtain a stable oxanorbornane intermediate. Subsequent dehydration and dehydrogenation using a physical mixture of acidic zeolites or resins in combination with metal on a carbon support then gives high yields of aromatics under relatively mild conditions.